Shoulder Surgery for RC Pathology, Arthropathy and Tumors - Nikolopoulos, Dimitrios D.; Safos, George K. (IntechOpen, 2022)
Orthopedic surgeons manage a wide array of shoulder injuries, including impingement syndrome, rotator cuff (RC) ruptures, shoulder fractures, scapular dyskinesis, and more. This book describes the pathology, evaluation, and management of shoulder and RC pathologies and highlights the role of an interprofessional team in the care of patients with these conditions. Chapters address such topics as shoulder biomechanics and pathology, arthroscopic evaluation and management of shoulder RC pathology, mini-open and arthroscopic balloon techniques for arthroplasty in severe arthritis, and difficult pathologies such as shoulder bone tumors and scapular dyskinesia.